2015
DOI: 10.1002/jmri.25114
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of radiation‐induced peripheral nerve injury in rabbits with MR neurography using diffusion tensor imaging and T2 measurements: Correlation with histological and functional changes

Abstract: DTI may be a more sensitive and accurate method to evaluate RIPNI compared with T2 measurements. FA and λ⊥ are promising quantitative indices in monitoring RIPNI. J. Magn. Reson. Imaging 2016;43:1492-1499.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Previous studies have shown in-vivo DTI to be predictive of nerve degeneration and regeneration in rabbit [ 16 18 , 20 ] and rat [ 8 10 ] sciatic nerve crush and laceration injury models. These studies demonstrated an initial FA decrease and RD increase in the sciatic nerve distal to the injury site immediately following sciatic nerve crush injury, presumably due to Wallerian degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown in-vivo DTI to be predictive of nerve degeneration and regeneration in rabbit [ 16 18 , 20 ] and rat [ 8 10 ] sciatic nerve crush and laceration injury models. These studies demonstrated an initial FA decrease and RD increase in the sciatic nerve distal to the injury site immediately following sciatic nerve crush injury, presumably due to Wallerian degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrated an initial FA decrease and RD increase in the sciatic nerve distal to the injury site immediately following sciatic nerve crush injury, presumably due to Wallerian degeneration. Thereafter, there was a period of significant FA increase and RD decrease due to regenerating myelin sheath [ 8 , 10 , 16 18 , 20 ] until reaching preinjury levels at 10 weeks. In our study, we did not find a significant RD decrease by week 13, which may indicate that the regenerative phase was incomplete at this time.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion‐weighted and diffusion‐tensor imaging (DTI) may be utilized in the peripheral nervous system. It has been shown experimentally that quantitative fractional anisotropy (FA) of DTI is closely associated with fiber density by direct histological correlation . Also, clinical evidence points to that DTI‐MRN improves the diagnostic accuracy over T 2 signal‐based contrast in a variety of nontraumatic peripheral neuropathies and is a promising surrogate measure of regeneration after traumatic nerve injury …”
mentioning
confidence: 99%
“…The pattern identified here is similar to recent DTI studies at lower field strength in patients with CTS 24 , 36 , 37 or other peripheral neuropathies. 31 , 38 , 39 Reduced FA and increased RD are also the predominant findings in experimental nerve injury models, where they correlate with histological markers of axon and myelin degeneration, 40 42 or the presence of inflammation-induced edema. 43 In humans, correlation of diffusion parameters with electrodiagnostic parameters thought to reflect axonal damage or demyelination reveal conflicting outcomes.…”
Section: Discussionmentioning
confidence: 95%